Effect of pH on Dimethylamine Borane Reduced Electroless Nickel Deposits on AISI/SAE 1045 Steel Surface (2019)
Abstract: Electroless Ni B coatings using DMAB-reduced plating baths at different pH conditions were formed on AISI/SAE 1045 carbon steel. Substrates were grit-blasted with alumina, generating a rough surface suitable for anchorage and nucleation of the coating. The surface of the substrates were examined at selected times of electroless treatment using scanning electron microscopy. The structure of the coating was studied by means of X-ray diffraction. A low-cost boron determination procedure was implemented in order to determine the amount of boron incorporated into the electroless coatings. Coatings nucleate faster at acid and neutral pH conditions; however, at the end of the plating process all coatings were adherent, with the typical morphology of Ni B electroless coatings. Substrates slightly corroded inside the plating bath at acid pH condition. The amount of boron into the coatings was approximately 2.15, 2.14 and 1.10% (wt%) for the acid, neutral and alkaline pH plating baths, respectively. Graphic Abstract: [Figure not available: see fulltext.]. © 2019, The Korean Institute of Metals and Materials.